EFFECT OF SUBLETHAL DOSE OF Najanaja SNAKE VENOM ON LEVELS OF SOME LIVER ENZYMES IN ALBINO MALE RATS - Taha Shawi Morad (Journal of Madenat Alelem University College, 2012)
The effects of (Najanaja) snake cobra venom on some liver enzymes in albino male rats have been investigated. The effects of a single sublethal dose of Najanaja snake venom (0.04μg/g) body weight on the activities of certain serum enzymes levels: aspartate aminotransferase (AST), alanine aminotransferase (ALT) and alkaline phosphatase (ALP) were studied. Samples from the serum were collected 3 and 24 h following venom dose intraperitonealy injected in male albino rats. The activities of these enzymes showed significant elevation compared to the control. Najanaja snake venom caused damage and hepatic dysfunction in enevomated male rats.